The Role of MSEs Loan in Achieving Inclusive Development in Bali Province - Putu Ayu Pramitha Purwanti; I Ketut Ksama Putra; Ni Putu Wiwin Setyari; Luh Gede Astariyani (Muhammadiyah University Press, 2022)
This study is aimed to look at the effect of credit sourced from the banking sector on the MSE’s income in each Regency/City of the Bali Province. This is important because the inclusive development index in Bali Province tends to increase, but the standard deviation for each Regency/City shows an increase until 2017. This condition indicates that development is still relatively unequal between Regencies/ City. By using the data from the Economic Survey 2016 from BPS and processed using the Propensity Score Matching (PSM) method, the results confirm that credit recipients have significantly higher incomes than those who do not receive. Theoretically, additional capital accumulation will encourage faster economic growth in relatively poor areas compared to richer areas, causing convergence in the two regions. The results of the analysis show that MSE actors in districts with lower growth get higher additional income, thus enabling equitable development in Bali.